Clinical evaluation of the Roche Elecsys® CMV IgG Avidity assay - Vauloup-Fellous, C. (Springer Berlin Heidelberg, 2014)
Congenital cytomegalovirus (CMV) infection has potentially severe consequences in newborns. The testing of pregnant women for CMV-specific antibodies may be useful for the identification of women at risk of transmitting the infection to the fetus. The determination of CMV IgG avidity helps to establish the timing of infection as IgG avidity matures during the course of infection. This study examines the performance of the Elecsys® CMV IgG Avidity assay using preselected samples from patients at different phases of CMV infection. The Elecsys® CMV IgG Avidity assay was tested at three sites using sequential samples from patients with recent primary CMV infection, as well as single samples from patients with recent primary or past CMV infection. The Elecsys® assay discriminated well between early (low avidity) and late (high avidity) phases of infection in sequential serum samples. Overall, 98.8 % of low-avidity samples corresponded to infection onset <180 days before sampling and 77.8 % of all high-avidity results corresponded to infection onset >90 days before sampling. The assay’s sensitivity was 90–97 %, with specificity ranging from 89 to 100 %, depending on the consideration of gray-zone avidity values. Single samples from recent primary or past infection showed similar distributions of avidity results. The Elecsys® CMV IgG Avidity assay results are in agreement with preselected samples from patients with primary or past CMV infection, showing that the test is an adequate predictor of the phase of infection.